Treatment adherence and effect of concurrent statin intensity on the efficacy and safety of alirocumab in a real-life setting: results from ODYSSEY APPRISE - Maciej Banach; José Luis López-Sendon; Maurizio Averna; Bertrand Cariou; Megan Loy; Garen Manvelian; Isabela Batsu; Yann Poulouin; Daniel Gaudet (Archives of Medical Science, 2021)
Introduction The phase IIIb open-label ODYSSEY APPRISE study prospectively assessed the safety and efficacy of alirocumab (a proprotein convertase subtilisin/kexin type 9 [PCSK9] inhibitor) in a real-life setting in high cardiovascular risk patients with heterozygous familial hypercholesterolemia or low-density lipoprotein cholesterol (LDL-C) not at goal despite maximally tolerated dose statins ± other lipid-lowering therapies (NCT02476006). This post-hoc analysis assessed patient adherence to statins and alirocumab, plus alirocumab efficacy and safety, according to concomitant statin intensity and prior ezetimibe usage.